2021
DOI: 10.3390/sports9110151
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: Niering, M.; Muehlbauer, T. Effects of Physical Training on Physical and Psychological Parameters in Individuals with Patella Tendinopathy: A Systematic Review and Meta-Analysis. Sports 2021, 9, 12

Abstract: The authors would like to correct an error in the name of the condition in the recently published paper [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In this sense, a review of this information indicates that the early FP is unfavorable for all strength classes and peak performance in isometric strength is seen in the late FP, whereas isokinetic strength peaks during ovulation. In addition, the same study explains that dynamic strength is optimal in the late FP [1,16].…”
Section: Introductionmentioning
confidence: 82%
“…In this sense, a review of this information indicates that the early FP is unfavorable for all strength classes and peak performance in isometric strength is seen in the late FP, whereas isokinetic strength peaks during ovulation. In addition, the same study explains that dynamic strength is optimal in the late FP [1,16].…”
Section: Introductionmentioning
confidence: 82%
“…Undulating training, as explored in various studies, demonstrated positive effects on both performance and muscle hypertrophy. 17 Additionally, it is noteworthy that the late follicular phase is considered optimal for peak performance in isometric maximal strength, while the late luteal phase, likely due to low estrogen levels, is less suitable. In contrast, dynamic maximal strength is most conducive during the late follicular phase, possibly due to elevated estrogen levels.…”
Section: Strengthmentioning
confidence: 99%
“…Heterogeneity of the integrated results was assessed by the Chi-squared test and I 2 index, and p < 0.05 was considered an indication of a significant difference. Following Niering M et al [19], heterogeneity can be interpreted as trivial (0 ≤ 40%), moderate (30 ≤ 60%), substantial (50 ≤ 90%), or considerable (75 ≤ 100%). If heterogeneity below 50%, a fixed effects model was used.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%